Neurally expressed Drosophila genes encoding homologs of the NSF and SNAP secretory proteins. - Ordway, R W (1994)
Several lines of investigation have now converged to indicate that the neurotransmitter release apparatus is formed by assembly of cytosolic proteins with proteins of the synaptic vesicle and presynaptic terminal membranes. We are undertaking a genetic approach in Drosophila melanogaster to investigate the functions of two types of cytosolic proteins thought to function in this complex: N-ethylmaleimide-sensitive fusion protein (NSF) and the soluble NSF attachment proteins (SNAPs). We have identified Drosophila homologs of the vertebrate and yeast NSF and SNAP genes. Both Drosophila genes encode polypeptides that closely resemble their vertebrate counterparts and are expressed in the nervous system; neither appears to be in a family of closely related Drosophila genes. These results indicate that the Drosophila NSF and SNAP genes are excellent candidates for mutational analysis of neurotransmitter release.